ANALYSIS OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM ON STUDENTS' INTERPERSONAL INTELLIGENCE - Sa’adaturrodiyah, Wenda Sustiana; Salma, Madian Fitri (Kitaba, 2024)
Optimizing the independent curriculum to improve the quality of education with the concept of simplifying and deepening the material and strengthening the Pancasila student profile. The aim of this research is to analyze the implementation of the independent curriculum on students’ interpersonal abilities. This research uses a qualitative research method which includes observation, interviews, analysis, and documentation. The results obtained indicate the influence of students’ interpersonal intelligence, which is affected by various indicators that support the success of the independent curriculum. These supporting indicators provide a significant impact on efforts to improve the quality of education. By updating the curriculum and optimizing the abilities of teachers and students in the learning process, a significant impact can be achieved with the concept of independent learning, simplification of objectives, and student-centered learning processes, thereby increasing students’ interpersonal intelligence.